Exploring the Correlation between Professors’ Use of ICT in Teaching and the Levels of Institutional Support - Drissia Chouit; Abdelhamid Nfissi; Hicham Laabidi (Journal of English Language Teaching and Linguistics, 2017)
The implementation of computer technologies in education has become the main goal of many educational reforms throughout the globe. Like many other nations, the Moroccan kingdom has understood the importance of using computers in schools and universities. For this reason, the Moroccan government has launched numerous projects aiming at the diffusion of Information and Communication Technologies (ICT) in education system. To prepare students to face the challenges of the twenty-first century, teachers should integrate computer technologies into their teaching practices. These modern technologies are very beneficial for both teachers and students. They help teachers develop professionally through the use of various ways of teaching. Students, on the other hand, can increase their achievements in the sense that they access several materials. The use of ICT in classroom practices is extremely significant for providing opportunities for students to function appropriately in an information age. This paper aims to examine the relationship between professors’ use of computer technologies for pedagogical purposes and the levels of encouragement provided by their institutions. Descriptive analysis of means, and standard deviations were used to analyse the collected data. Also, inferential statistics, mainly Pearson Product Moment Correlation, were employed to account for this correlation. The findings revealed that there is a strong positive correlation between the two variables, r = 0.59, p < .01.